Bridging the gray digital divide: A cross-cultural qualitative study on digital inclusion and healthy aging in Germany, Japan, and Thailand - I-Chun Chen; Anuchit Phanumartwiwath (Telematics and Informatics Reports)
This study explores the global challenge of digital inclusion for healthy aging through a cross-cultural analysis of Germany, Japan, and Thailand. Using semi-structured interviews with twenty-four stakeholders and thematic analysis via ATLAS.ti 9.0 software, we identify three core themes: “Digital Literacy and Barriers to Inclusion,” “Facilitators of Digital Inclusion,” and “Community-Based Health and Technology Support.” Findings reveal that socio-cultural, psychological, and infrastructural factors shape distinct regional approaches: Germany's community-based 'Zentrum Plus' centers, Japan's volunteer networks, and Thailand's government-led initiatives. These case studies demonstrate the necessity of culturally sensitive strategies to bridge the “gray digital divide.” By examining how digital media cultures (i.e., technology adoption patterns shaped by sociocultural norms) mediate psychosocial outcomes (e.g., self-efficacy, social connectivity) in aging populations, the study contributes to interdisciplinary research at the intersection of gerontechnology, media studies, and public health. Specifically, we advance two frameworks: 1) a cultural relativity model of digital literacy acquisition and 2) a psychosocial impact matrix linking technology access to mental well-being metrics. Policy recommendations include public-private partnerships, volunteer-driven literacy programs, and rural digital infrastructure investment.